Pengaruh Motivasi Belajar Dan Lingkungan Belajar Terhadap Hasil Belajar Mahasiswa pada Mata Kuliah Pendidikan IPS di SD pada Program Studi S-1 PGSD Kelompok Belajar Kota Jambi Masa Registrasi 2020.1 - Mahyudin Mahyudin (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The purpose of this study was to analyze (1) the effect of learning motivation on student learning outcomes in social studies courses in elementary school in the PGSD S1 Study Program in the Jambi City Study Group 2020.1, (2) The effect of the learning environment on student learning outcomes in subjects Social Studies lecture at elementary school in the PGSD S1 Study Program Study Group Jambi City Registration Period 2020.1, and (3) The influence of learning motivation and learning environment on student learning outcomes in Social Sciences Education courses in SD on the PGSD S1 Study Program Study Group Jambi City 2020 Registration Period. Research conducted by researchers is a survey research method. The sampling technique in this study is saturated sampling. Where, all populations were sampled as a study, totaling 21 students. The data collection techniques in this study were questionnaire and documentation. The results showed that (1) Learning motivation has a significant effect on student learning outcomes in Social Studies courses in elementary schools in the S1 Study Program PGSD Study Group Jambi City Registration Period 2020.1. Based on the analysis it is known that the value of tcount> ttable, which is 5.999> 2.10092 at a significance level of 0.05. Furthermore, the contribution of learning motivation variables to learning outcomes is 65.4% and the remaining 34.6% is influenced by other factors not examined, (2) The learning environment has a significant effect on student learning outcomes in Social Studies courses in elementary school in the Study Program S-1 PGSD Jambi City Study Group Registration Period 2020.1. Based on the analysis it is known that the value of tcount> ttable, which is 3.718> 2.10092 at a significance level of 0.05. Furthermore, the contribution of learning environment variables to learning outcomes is 42.1% and the remaining 57.9% is influenced by other factors not examined, and (3) learning motivation and learning environment have a significant effect on student learning outcomes in Social Studies courses in Elementary School in PGSD Undergraduate Study Program Jambi City Study Group Registration Period 2020.1. Based on the analysis it is known that the value of Fcount> Ftable, which is 23.539> 3.55 at a significance level of 0.05. Furthermore, the contribution of learning motivation and learning environment variables simultaneously to learning outcomes is 72.3% and the remaining 27.7% is influenced by other factors not examined.